2013
DOI: 10.3897/zookeys.298.4834
|View full text |Cite
|
Sign up to set email alerts
|

A relict lineage and new species of green palm-pitviper (Squamata, Viperidae, Bothriechis) from the Chortís Highlands of Mesoamerica

Abstract: A new species of palm-pitviper of the genus Bothriechis is described from Refugio de Vida Silvestre Texíguat in northern Honduras. The new species differs from congeners by having 19 dorsal scale rows at midbody, a bright green dorsal coloration in adults, the prelacunal scale fused to the second supralabial, and in representing a northern lineage that is sister to Bothriechis lateralis, which is distributed in Costa Rica and western Panama and is isolated from the new taxon by the Nicaraguan Depression. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
(57 reference statements)
3
9
1
Order By: Relevance
“…Single mitochondrial gene phylogenies lacked the resolution of the Homblocks alignment, but similarly supported this conflicting relationship ( Figure S3 in Appendix S4). This topology is consistent with other mitochondrially driven phylogenies (Castoe et al, 2009;Daza et al, 2010;Doan et al, 2016;Townsend et al, 2013).…”
Section: Mitochondrial Analysessupporting
confidence: 90%
See 1 more Smart Citation
“…Single mitochondrial gene phylogenies lacked the resolution of the Homblocks alignment, but similarly supported this conflicting relationship ( Figure S3 in Appendix S4). This topology is consistent with other mitochondrially driven phylogenies (Castoe et al, 2009;Daza et al, 2010;Doan et al, 2016;Townsend et al, 2013).…”
Section: Mitochondrial Analysessupporting
confidence: 90%
“…It is therefore unclear whether the incongruences in these results are due to differences in analytical approach and total sequence data, or if they reflect biological discordance in the system. Additionally, the description of several new species, some of which add biogeographic-phylogenetic conflict (Figure 1c), further call into question the evolutionary processes shaping this (Campbell & Smith, 2000;Doan et al, 2016;Solórzano, Gómez, Monge-Nájera, & Crother, 1998;Townsend, Medina-Flores, Wilson, Jadin, & Austin, 2013).…”
Section: One Middle American Group With a Complex Biogeographic Distrmentioning
confidence: 99%
“…Excluding B. schlegelii, the majority of Bothriechis are highland species, which typically inhabit restricted ranges (Campbell & Lamar 2004). In the case of B. guifarroi, B. rowleyi, and B. supraciliaris, these ranges may consist of a small number of known localities confined to a single highland region (Solórzano et al 1998;Campbell & Lamar 2004;Townsend et al 2013). Because of the limited ranges and disjunct distributions of these species, the evolutionary relationships of these snakes can provide insight into regional patterns of dispersal, diversification, and speciation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent phylogenies using multilocus mitochondrial datasets have inferred B. lateralis as a sister lineage to the northern Middle American highland clade with B. nigroviridis as sister to all of the highland Bothriechis lineages (Castoe & Parkinson 2006;Castoe et al 2009;Daza et al 2010). Most recently, Townsend et al (2013) reconstructed a phylogeny based on four mitochondrial loci in conjunction with the species description of B. guifarroi and found a (B. nigroviridis (B. lateralis, B. guifarroi)) clade sister to the northern Middle American highland clade. This suggested that divergence of the northern and southern Middle American highland Bothriechis groups may be more recent than previously estimated (Townsend et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2). The species exhibiting MBSSD (B. marchi, B. rowleyi and B. thalassinus) are all members of the Nuclear Central America group of palm pitvipers (Townsend et al, 2013), although they share no clear pattern in behaviour of SSD. This suggests that the interplay of underlying evolutionary selective forces might be particularly complex in this group of species, likely with some as-yet undetermined factor having an influential role in the evolution of male body size.…”
Section: Origins Of Ssdmentioning
confidence: 99%